2018
DOI: 10.1002/celc.201801128
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electrospun Carbon−Carbon Composite and Commercial Felt for Their Activity and Electrolyte Utilization in Vanadium Redox Flow Batteries

Abstract: A low cost highly active carbon−carbon composite fiber felt was produced by electrospinning a mixture of polyacrylonitrile and carbon black powder using poly acrylic acid as a binder for high carbon black loading. The newly designed high‐surface area electrode material showed promising results for use as electrode material for both the negative and positive half‐cell of vanadium redox flow batteries. Battery test results demonstrated promising performance for the electrospun carbon fibers at current densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Finally, Fetyan and Banerjee et al very recently published two on pore-scale characterization of carbon-carbon composite electrospun RFB electrodes in which they used pore-network modeling to compute effective transport properties of the electrode. 30,31 However, their study is focused on characterization of RFB electrodes rather than investigating the pore-scale effects of overall performance. A similar study has also been reported by Kok et al but is also limited to computing effective mass transfer coefficients of flow battery electrodes using LBM simulations.…”
mentioning
confidence: 99%
“…Finally, Fetyan and Banerjee et al very recently published two on pore-scale characterization of carbon-carbon composite electrospun RFB electrodes in which they used pore-network modeling to compute effective transport properties of the electrode. 30,31 However, their study is focused on characterization of RFB electrodes rather than investigating the pore-scale effects of overall performance. A similar study has also been reported by Kok et al but is also limited to computing effective mass transfer coefficients of flow battery electrodes using LBM simulations.…”
mentioning
confidence: 99%
“…Since the specific surface area of pure PAN nanofibers (fiber diameter ~ 230 nm) was ~ 33 times higher compared to the commercial carbon felts (~ 10 μm fiber diameter 37 ), it could be attributed to its 40-fold smaller fiber diameter. However, the outstanding specific surface area of CB-loaded PAN nanofibers could not only be attributed to their smaller fiber diameter (they had even larger diameter than pure PAN nanofibers; see Fig.…”
Section: Bet Surface Areamentioning
confidence: 97%
“…Electrodes play a crucial role on the cell performance, because both negative and positive redox reactions of active ions take place on the electrode surface. Presently, graphite felt is employed as the most widely utilized electrode owing to relatively large surface area, high electrical conductivity, wide operation potential and high chemical stability in acidic electrolyte . Depending on the source of the material, fiber thickness, porosity, graphitization degree and surface treatment, physical as well as electrochemical properties of graphite felts may vary.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, graphite felt is employed as the most widely utilized electrode owing to relatively large surface area, high electrical conductivity, wide operation potential and high chemical stability in acidic electrolyte. [10][11][12][13] Depending on the source of the material, fiber thickness, porosity, graphitization degree and surface treatment, physical as well as electrochemical properties of graphite felts may vary. Graphite felt can be classified by the precursor materials: polyacrylonitrile-based graphite felt (PANGF), rayon-based graphite felt (RGF), pitch-based graphite felt (PGF), etc.…”
Section: Introductionmentioning
confidence: 99%